Witness and Silence in Neuromarketing: Managing the Gap between Science and Its Application. (January 2020) - Brenninkmeijer, Jonna; Schneider, Tanja; Woolgar, Steve
Over the past decades commercial and academic market(ing) researchers have studied consumers through a range of different methods including surveys, focus groups, or interviews. More recently, some have turned to the growing field of neuroscience to understand consumers. Neuromarketing employs brain imaging, scanning, or other brain measurement technologies to capture consumers' (brain) responses to marketing stimuli and to circumvent the "problem" of relying on consumers' self-reports. This paper presents findings of an ethnographic study of neuromarketing research practices in one neuromarketing consultancy. Our access to the minutiae of commercial neuromarketing research provides important insights into how neuromarketers silence the neuromarketing test subject in their experiments and presentations and how they introduce the brain as an unimpeachable witness. This enables us conceptually to reconsider the role of witnesses in the achievement of scientific credibility, as prominently discussed in science and technology studies (STS). Specifically, we probe the role witnesses and silences play in establishing and maintaining credibility in and for "commercial research laboratories." We propose three themes that have wider relevance for STS researchers and require further attention when studying newly emerging research fields and practices that straddle science and its commercial application.